The impact of predictive nursing on the postoperative complications and quality of life in patient experienced radical cystectomy and cutaneous ureterostomy (预见性护理对膀胱全切输尿管皮肤造口患者术后并发症及生活质量的影响) - HUANG Weixing (黄微星); WAN Lingjun (万玲君); HUANG Huan (黄幻); ZHANG Beibei (章贝贝) (中西医结合护理)
Objective To explore the impact of predictive nursing on the postoperative complications and quality of life of inpatients experienced radical cystectomy and cutaneous ureterostomy. Methods Patients with muscle-invasive bladder cancer admitted to the Department of Urology, Taizhou Hospital affiliated to Zhejiang University from March 2018 to May 2021 were selected as the research objects. According to the random number table method, the patients were divided into two groups, with 36 cases in each group. Factors such as postoperative loss to follow-up were excluded, 29 patients received routine nursing during the perioperative period, which was the control group. Another 34 patients received predictive nursing care, as the intervention group. Medical Coping Style Questionnaire (MCMQ) was used to evaluate patients' coping style after stoma, self-care ability Scale (ESCA) was used to evaluate patients' self-care ability, and Health Survey Short Form (SF-36) was used to evaluate patients' quality of life. Results The overall incidence of complications in the intervention group was lower than that in the control group at 6 months after surgery (14. 71% vs. 48. 28%, P＜0. 01). Patients in the intervention group achieved higher a score of facing coping style in ESCA compared with that in the control group(P＜0. 01). Factor scores of health knowledge level, self-care ability and sense of self-care in the intervention group were higher than those in the control group (P＜0. 05). The factor scores of SF-36 in the intervention group were higher than those in the control group (P＜0. 05). Conclusion Perioperative predictive nursing for patients undergoing radical cystectomy and cutaneous ureterostomy can effectively reduce the occurrence of complications, make patients actively cope with postoperative life, and improve their self-care ability and quality of life. (目的 观察预见性护理对接受膀胱全切输尿管皮肤造口手术患者术后并发症及生活质量的影响。方法 采用前瞻性研究, 选取2018年3月—2021年5月浙江省台州医院泌尿外科收治的肌层浸润性膀胱癌患者为研究对象, 根据随机数表法将患者分为两组, 各36例, 排除术后失访等因素, 最终纳入63例进行分析。其中29例患者在围手术期接受常规护理, 设为对照组; 另34例患者给予预见性护理, 设为干预组。观察两组患者术后并发症发生率, 采用医学应对方式问卷(MCMQ)评估患者造口后的应对方式、自我护理能力量表(ESCA)评估患者的自我护理能力、健康调查简表(SF-36)评估患者的生存质量。结果 术后6个月时, 干预组并发症总发生率14. 71%(5/34), 低于对照组的48. 28%(14/29), 差异有统计学意义(P＜0. 01); 干预组患者MCMQ问卷面对量表评分高于对照组(P＜0. 01); 干预组患者ESCA量表的健康知识水平、自我护理技能、自护责任感评分高于对照组(P＜0. 05); 干预组患者SF-36量表各维度得分均较对照组升高, 差异有统计学意义(P<0. 05)。结论 对接受膀胱全切输尿管皮肤造口术患者围手术期进行预见性护理, 可有效降低并发症发生, 更能使患者积极应对术后造口生活, 提升其自我护理能力及术后生存质量。)